2014
DOI: 10.1186/1297-9716-45-16
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of mammary epithelial cells to the immune response during early stages of a bacterial infection to Staphylococcus aureus

Abstract: To differentiate between the contribution of mammary epithelial cells (MEC) and infiltrating immune cells to gene expression profiles of mammary tissue during early stage mastitis, we investigated in goats the in vivo transcriptional response of MEC to an experimental intra mammary infection (IMI) with Staphylococcus aureus, using a non-invasive RNA sampling method from milk fat globules (MFG). Microarrays were used to record gene expression patterns during the first 24 hours post-infection (hpi). This approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 72 publications
2
72
0
1
Order By: Relevance
“…For example, S100A12 is induced in response to E. coli or S. aureus infection of mammary tissue (57,58). S100A12 is also induced in response to nontypeable Haemophilus influenzae and Streptococcus pneumoniae infection leading to acute otitis media (59).…”
Section: Discussionmentioning
confidence: 99%
“…For example, S100A12 is induced in response to E. coli or S. aureus infection of mammary tissue (57,58). S100A12 is also induced in response to nontypeable Haemophilus influenzae and Streptococcus pneumoniae infection leading to acute otitis media (59).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also stated that most leukocytes are mobilized from the bloodstream into the mammary tissue after changes in the capillary permeability. Milk from cows with intramammary infections may show increased numbers of immune cells, leading to a predomination of neutrophils, followed by macrophages and lymphocytes, while the number of epithelial cells remains unchanged (12,13). Previous study showed that bovine viral diarrhea affects SCC (8), the lack of information concerning infectious diseases motivated the present study on the relationship between milk composition and quality on dairy cattle with tick fever.…”
Section: Babesia Bovismentioning
confidence: 95%
“…In Argentina, it has been reported that dairy cows experimentally infected by an attenuated strain of A. marginale showed reduction of milk production, as well as fever, sanguíneo hacia el tejido mamario tras cambios en la permeabilidad capilar. La leche de vacas con infecciones intra-mamarias puede presentar un mayor número de células inmunes, lo que lleva a un predominio de neutrófilos, seguido por macrófagos y linfocitos, mientras que el número de células epiteliales permanece sin cambios (12,13). Un estudio anterior mostró que la diarrea viral bovina afecta el valor de SCC (8); la falta de información respecto a las enfermedades infecciosas motivó el presente estudio sobre la relación entre la composición y calidad de la leche en el ganado lechero con fiebre por garrapatas.…”
Section: Babesia Bovisunclassified
“…They not only act as physical barriers but also are capable of producing inflammatory mediators. While interacting with invading bacteria, mammary epithelial cells generate multiple inflammatory cytokines . However, an excessive inflammatory response in the mammary gland may cause tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…While interacting with invading bacteria, mammary epithelial cells generate multiple inflammatory cytokines. 5, 6 However, an excessive inflammatory response in the mammary gland may cause tissue damage.…”
mentioning
confidence: 99%